Caracterización e investigación de nuevas tecnologías para el uso de aguas de producción petrolera en riego de cultivos (2024)
This research was carried out through the review of new technologies to comply with the best process for its use and compliance with oil production waters for use in crop irrigation where it is mainly required to obtain the best technologies for the fluid leaving conventional reservoirs. used in the irrigation of crops, determining parameters for the correct irrigation of production waters, which were pH, salinity, toxicity due to ions, fats and suspended solids and alkalinity, among others (Rojas, 2021).